Study about CIGS-based Solar Cells with ZNS Buffer Layer: A Numerical Modeling and Simulation Approach - Adama Sylla; Siaka Toure; Jean-Pierre Vilcot (Research Highlights in Science and Technology Vol. 6, 2023)
In this chapter, we examine how the thin-film CIGS solar cells performances are modified when replacing the conventional toxic by buffer layers. is one of the most promising semiconductor materials for photovoltaic conversion based on polycrystalline thin-films. It is a semiconductor of great attraction in recent years as thin-film solar cell absorber material. Usually a buffer layer of cadmium sulphide is used in high efficiency solar cells based on . Numerous studies have been done to use Cd-free buffer layers due to cadmium toxicity. Our work focuses on this type of CIGS-based solar cells where is replaced by a buffer layer. In this contribution AFORS-HET software is used to simulate polycrystalline thin-film solar cell where the key parts are p-CIGS absorber layer and n-ZnS buffer layer. The role of the buffer layer is to be as much transparent as possible, allowing a maximum sunlight absorption in the absorber layer while maintaining a low interface recombination rate. To maximise conversion efficiency, it has been found that the doping concentrations of the absorber and buffer layers, as well as their thickness and Ga content, are critical component features. We find a maximum conversion efficiency of with a short-circuit current of , an open circuit voltage of , and a fill factor of .